GHIRAH BERPOLITIK PEREMPUAN FATAYAT NU DI KABUPATEN ASAHAN - Agda Maghrusyah, Nafisa; Khoir Rambe, Uqbatul (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study examines the political enthusiasm of female cadres of Fatayat Nahdlatul Ulama (NU) in Asahan Regency, female cadres of Fatayat Nahdlatul Ulama (NU) in Asahan Regency show a strong enthusiasm (passion) in politics even though women's representation in the legislature is still limited. This study aims to analyze the political enthusiasm of female cadres of Fatayat NU, the driving factors, and the obstacles they face. Using a descriptive qualitative approach and field research methods through interviews, documentation, and observation, the study found that Fatayat NU cadres are active in various strategic positions in government and elections. Their political enthusiasm is motivated by an awareness of gender justice, while the main obstacles come from limited human resources and patriarchal culture. To overcome this, Fatayat NU runs a cadre development, advocacy, and research program to strengthen the political capacity of its female cadres.